Electrochemical Reduction of CO2 (ERCO2) on Pb Electrocatalysts using Mn3O4 as Anode - V. S. K. Yadav (17727660) (2025)
The electrochemical reduction of carbon dioxide (ERCO2) to chemical feedstock and fuels is a promising strategy for reducing excessive carbon dioxide emissions. There are various benefits of converting CO2 to a single product and Pb is one of the active and efficienct catalyst for reducing CO2 to HCOOH. The current work used the electro‐deposition method to produce manganese oxide (Mn3O4) (nano particle flakes) and highly active, low‐cost lead (Pb) catalysts with a variety of morphologies (Nano crystal Flakes, Nano wires, and Nano crystal sheets). For the first time, the Mn3O4 catalyst was employed as the anode in the water oxidation process to produce protons, and the electrocatalytic effects of Mn3O4 and Pb on the ERCO2 reaction were investigated. The influence of CO2 reduction on catalyst loading is investigated and the lone product HCOOH is detected on the produced Pb catalysts. Using a systematic electrochemical study, the final product of the ERCO2 reaction is identified and measured. The maximum Faradaic efficiency was measured on Pb (nano crystal flakes) at −1.003 V, yielding efficiency of 77.32 % (10 min) in 1 mg/cm2 catalyst loading and 78.4 % on nano wires (10 min) at −1.003 V in 2 mg/cm2 catalyst loading, respectively. More specifically, it is discovered that the reaction selectivity and efficiency of CO2 electroreduction to HCOOH are highly influenced by the morphology and loading of the catalyst. These results provide an intimate understanding of water oxidation on Mn3O4 and CO2 electroreduction on Pb catalyst. Other Information Published in: ChemElectroChem License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/celc.202400527